2012
DOI: 10.1056/nejmoa1112066
|View full text |Cite|
|
Sign up to set email alerts
|

Childhood Outcomes after Hypothermia for Neonatal Encephalopathy

Abstract: BACKGROUND We previously reported early results of a randomized trial of whole-body hypothermia for neonatal hypoxic–ischemic encephalopathy showing a significant reduction in the rate of death or moderate or severe disability at 18 to 22 months of age. Long-term outcomes are now available. METHODS In the original trial, we assigned infants with moderate or severe encephalopathy to usual care (the control group) or whole-body cooling to an esophageal temperature of 33.5°C for 72 hours, followed by slow rewar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
368
3
16

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 643 publications
(392 citation statements)
references
References 21 publications
5
368
3
16
Order By: Relevance
“…17 However, the rate of mildly abnormal outcome (33.3%) was higher compared with literature and the rate of abnormal outcome (1 death, 11.1%) was lower than reported trials. 5,17 This discrepancy is most likely due to the small sample size included in this particular study, as the overall outcome of neonatal HIE treated with TH at our institution is similar to published data. Due to the low number of patients, scores can only be used to describe individuals but predictive modeling will be implemented for a planned larger cohort.…”
Section: Hgbsupporting
confidence: 68%
See 1 more Smart Citation
“…17 However, the rate of mildly abnormal outcome (33.3%) was higher compared with literature and the rate of abnormal outcome (1 death, 11.1%) was lower than reported trials. 5,17 This discrepancy is most likely due to the small sample size included in this particular study, as the overall outcome of neonatal HIE treated with TH at our institution is similar to published data. Due to the low number of patients, scores can only be used to describe individuals but predictive modeling will be implemented for a planned larger cohort.…”
Section: Hgbsupporting
confidence: 68%
“…4 Although early studies showed that TH decreased rates of both mortality and disability, recently published long-term outcomes have demonstrated significance only for decreased mortality rates. 5 In addition, a recent meta-analysis advocated refinement of patient selection and TH duration whereas others have suggested that currently excluded neonates be considered in future trials. 6,7 Thus a need for further optimization of TH remains.…”
Section: Introductionmentioning
confidence: 99%
“…1 Follow-up studies of large randomized trials have shown that infants with hypoxic-ischemic encephalopathy treated with therapeutic hypothermia showed a reduction in death, cerebral palsy and disability, and improved neurocognitive functioning that persisted into middle childhood. [1][2][3][4] The major challenge for the future is that current protocols for therapeutic hypothermia are partially neuroprotective, with a number needed to treat of eight. 1 In part, partial protection is likely related to the formidable clinical difficulties involved in starting hypothermia within the optimal window of opportunity.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its relatively high incidence among newborns with cerebral injury, limited therapies are available for its prevention and treatment 2, 3. Furthermore, unlike the aging adult brain, neuronal death in the immature CNS is not only a pathological cellular event of brain injury but also a biological process required for early normal brain development 4.…”
Section: Introductionmentioning
confidence: 99%